The Northwestern University Novel Urology Residency Curriculum: Updated Outcomes from a 13-Year Experience with Flexible Residency Training and Electives. Issue 2 (22nd March 2022) - Cooley, Lauren Folgosa; Isaacson, Dylan; Vo, Amanda X.; Ross, Kelly; Kielb, Stephanie
Abstract: Introduction: We evaluated educational outcomes and satisfaction following institution of a novel, flexible and urology-driven resident curriculum. Methods: A new urology resident curriculum was instituted at Northwestern University in 2006. Rotation schedules and resident electives were recorded annually. Operative case logs and American Urological Association In-Service Examination scores were collected prospectively. Residents and faculty rated satisfaction with the residency program on a 5-point Likert scale from "poor" to "outstanding." Differences in cases logged, In-Service Examination scores and satisfaction ratings under the new and prior curricula were compared. Results: Curriculum changes included full 5-year urology oversight of the residency curriculum by the program director, 8 months of urology rotations in the first postgraduate year and 2 months of general surgery during the second postgraduate year. General surgery rotations were modified annually based on educational rationale and feedback. Cases logged per resident and In-Service Examination scores were comparable between old and new curricula groups. All residents matriculating under the new curriculum took and passed their written boards. The percentage of faculty and residents describing the program as "outstanding" increased from 50% in 2004‒2005 to 82% in 2017‒2018. Program satisfaction increased significantly when comparing the first and last 6 years (percent rating "outstanding": 56.1±2.1% vs 71.6±10.0%, p=0.028). Conclusions: After 13 years with the novel curriculum, resident case numbers and In-Service Examination scores remained similar while faculty/resident satisfaction increased. Direct control of general surgery rotations enabled adjustments based on educational rationale. These results demonstrate that a urology-directed and flexible residency program can be instituted without compromising learner outcomes.